The eﬀects of acupressure, LV3 point on fetal heart rate pattern, during fetal non stress test: A randomized clinical trial - Mahbubeh Tabatabaeichehr; Massumeh Eftekharian; Elham Sharifian; Sakineh Nazari; Mahbubeh Ghorbani; Maryam Bagheri (Mashhad University of Medical Sciences, 2019)
Introduction: The fetal heart rate monitoring is actually the first test to evaluate the health of fetus. Mother's mental condition impacts the fetal heart rate pattern. Acupressure acts on the basis of acupuncture points, and according to neuro-hormonal theory, acupressure secretes enkephalin and reduces the level of stress and anxiety of the mother. Therefore, this study was performed with aim to determine the effects of acupressure, LV3 point on fetal heart rate parameters and fetal movements during non-stress test. Methods: This clinical trial was performed on 84 nulliparous women with gestational age of 40-42 weeks in Bojnurd Bentolhoda hospital in 2018. The subjects were randomly divided into intervention and control groups. In the intervention group, pressure was applied on the LV3 point in each leg for 2.5 min and in the control group, around the point was touched. Fetal non-stress test was performed for 20 minutes in two steps for 10 min. Data was analyzed by the SPSS software (version 24), and Chi-square, Fisher exact and independent t-tests. PResults: In the intervention group, mean difference of the variables of baseline fetal heart rate, the number of increase in baseline fetal heart rate, the increase in baseline fetal heart rate, and the number of fetal movements were statistically significant and was more in the second10 minutes after the intervention than the first10 minutes (p<0.05). Mean difference of the variables of increase in baseline fetal heart rate and the number of fetal movements during the first and second stages was more in the intervention group than the control group, and  this difference was statistically significant (p<0.05). Conclusion: Acupressure can improve fetal heart rate parameters and movements, and decrease the false non-reactive cases due to maternal stress and unnecessary interventions following it.